Rare Pseudopapillary Neoplasm of the Pancreas: A 10-Year Experience. (17th September 2021) - Jena, Suvendu Sekhar; Ray, Samrat; Das, Sri Aurobindo Prasad; Mehta, Naimish N; Yadav, Amitabh; Nundy, Samiran
Abstract : Introduction . The solid pseudopapillary epithelial neoplasm (SPN) is a rare form of pancreatic neoplasm with an incidence of 2-3% of all pancreatic tumours. The recent increase in incidence is attributed to the increasing use of imaging techniques for nonspecific abdominal complaints. We report our institutional experience in the management of this tumour over the last decade. Method . We retrospectively analyzed from a prospectively maintained database of patients from January 2011 to December 2020 who were operated upon for SPN. All the patients were followed till date. Results . Of 479 patients operated on for various types of pancreatic tumours during this period, 15 (3.1%) had SPN. The mean age of presentation was 28 years with a female preponderance (12/15, 80%). The most common location was the body and tail of the pancreas (66%), and the mean size was 6.4 cm (2–15 cm). The tumour extent was defined as 'borderline resectable' in 20% of cases. Distal pancreatectomy was done in 11 patients with spleen preservation in 3. R 0, R 1, and R 2 resection were done in 12, 2, and 1 patient(s), respectively. The operative mortality was 6.7%. All the patients are doing well on follow-up. Conclusion . SPN is a low-grade malignant tumour with a strong female predilection. Clinical manifestations have no specificity, imaging examination only contributes tumour location, and the final diagnosis rests on pathology. Surgery is the main modality of treatment and carries a good prognosis.